An Industry 4.0 approach to assembly line resequencing - Rossit, Daniel Alejandro (2019)
Contemporary assembly line systems are characterized by an increasing capability to offer each client a different product, more tuned to her needs and preferences. These assembly systems will be heavily influenced by the advent of Industry 4.0 technologies, enabling the proposal of business models that allow the late customization of the products, i.e., the customer can modify attributes of its product once the production of it is started. This business model requires that the manufacturing tools are able to make decisions online and negotiate with the customer the changes that can be carried out, according to the workload flowing through the production system. In this work, we analyze the possibilities and limitations of this new paradigm. First, we show that Industry 4.0 systems can autonomously manage the production management process, and then, we present a framework based on tolerance planning strategies (tolerance scheduling problem), to determine which changes can be carried out. The ability of resequencing the production process is also implemented in the case that the operations associated with late customization allow it (i.e., when intermediate buffers are available). This establishes a parallelism with the problem of non-permutation flow shop. We finally discuss future developments necessary to implement these procedures.